Structural alterations of the bladder induced by detrusor instability. experimental study in rabbits - Amaro, Joao L. [UNESP]; Balasteghin, Karina T.; Padovani, Carlos R.; Montenegro, Renata (International Braz J Urol : Official Journal Of The Brazilian Society Of Urology, 2005)
The aim of this study was to evaluate the histopathological and immunohistochemical alterations induced by detrusor instability in the bladder of rabbits submitted to partial bladder outlet obstruction. Thirty male Norfolk rabbits were divided into 2 groups, a clinical control and a group with detrusor instability. Urine culture, cystometric study, histopathological and immunohistochemical analysis were performed in all animals prior to surgery (M1) and 4 weeks after-surgery (M2). Partial obstruction (G2) resulted in a 2.5 fold increment (p < 0.05) in bladder weight when compared to control (G1). Four weeks after surgery, 93% of animals in G2 developed cystitis. Partial obstruction resulted in detrusor instability at M2 and bladder capacity was significantly increased (p < 0.05) from M1 to M2. The incidence of mild to moderate mucosal and adventitious fibrosis at M2 was higher in G2 (p < 0.05) when compared to G1. Inflammatory reaction at M2 was statistically higher (p < 0.05) in G2. There was no difference in muscular hypertrophy between M1 and M2 in G1. However, 67% of G2 bladders showed a moderate to intense muscular hypertrophy at M2. Hyperplasia of the epithelium was also increased in G2 when M1 and M2 were compared (p < 0.05). Detrusor instability induced by partial bladder outlet obstruction caused significant histopathological and immunohistochemical alterations in the bladder of rabbits.
Keywords: Bladder; Rabbits; Bladder outlet obstruction; Histopathology